Simple Oxidimetric Methods for Determination of Stavudine or Lamivudine - Sarma, C.S.N.; Kamala Sastri, C.; Sastri, C.S.P. (Asian Journal of Chemistry, 2010)
Three simple and sensitive visible spectrophotometric methods (A, B and C) have been described for the estimation of stavudine (STU) or lamivudine (LAM) in pure state and in unit dosage forms. These are based on the oxidation of STU or LAM with oxidant (potassium permanganate. MnO–4, method-A; potassium permanganate- sodium metaperiodate, MnO–4-IO–4, method-B; ferric chloride. Fe(III), method-C), followed by the estimation of unreacted oxidant with fast green FCF (FG FCF, method-A) or product formed [aldehyde with 3-methyl benzothiazolinone hydrazone (MBTH), method-B; Fe(II) with potassium ferricyanide [Fe(CN)6]3–, method-C. The variable parameters of all these methods have been optimised and the chemical reactions involved are presented. The results obtained in these methods are statistically validated and recoveries range from 99.07 to 99.95%